Clean Energy Consumption and Economic Growth: A Case Study for Developing Countries - Fotourehchi, Zahra (International Journal of Energy Economics and Policy, 2017)
In this paper, we analyze the long-run causality relationship between renewable/clean energy consumption and economic growth during the period 1990-2012 for 42 developing countries, under the Canning and Pedroni (2008) long-run causality test, which indicates that there is long-run positive causality running from renewable energy to real GDP. This means that for developing countries where renewable energy consumption has a positive long-run causal effect on real GDP, renewable energy dependent conservation policies have prohibitive impact on economic growth. Moreover, government's\energy policies should encourage the development of clean energy sector instead of polluted energy sector for energy security and environmental challenges. Keywords: Renewable energy; Economic growth; Developing countries JEL Classifications: O10; Q20